Alternative finance: definition, sources and implications for the financial sector - Chabaya, Bothwell (My University, 2020)
The research will seek to highlight the sources of alternative finance and in the same vain highlight the structural problems of ‘’tainted intermediation’’ brought about as a result of the rise of Alternative Finance. It seeks to introduce a framework for regulatory thinking and approach in response to the emergence of alternative finance especially given that it is a new and developing phenomenon. The research will assist with further studies in the area of financial inclusion in the emerging economies as a result of alternative finance as well as the role and impact of alternative finance in the democratization of the financial sector. The study seeks to contribute in highlighting the main sources of alternative finances from the different types offered in the financial sector. It goes further to explore whether these sources of alternative finance result in reintermediation or disintermediation 15 answering the questions of who and what the intermediator is because of alternative finance. This exploration would highlight the problem of ‘’tainted intermediary’’, as well as lead to an introduction of how regulators and policymakers should frame their thought process and approach in the development of regulation governing the operations of new and alternative finance. Because alternative finance is a new and developing phenomenon the study will assist in further study of the area by the academic community from insights provided.
A research report submitted in partial fulfilment of the requirements for the degree of Master of Management in Finance and Investments to the Faculty of Commerce, Law and Management, University of the Witwatersrand, Wits Business School, Johannesburg, 2020
Keywords: Alternative finance; Tainted intermediation’; Financial inclusion; Financial sector; SDG-8: Decent work and economic growth